Analisa Penerapan Metode Imprest Fund dan Fluctuating Balance Terhadap Petty Cash Menurut PSAK No. 2 di PT Syngenta Indonesia - Lailatul Nazilah; Eko Prasetyo (Jurnal Multidisiplin Madani, 2022)
Research to find out the actual events in the reality of the petty cash recording system with the deposit fund system at PT Syngenta Indonesia Malang and Kediri and the Fluctuating Balance System at PT Syngenta Indonesia Kediri as well, as problems that arise from two different systems but with the same report results . The method used in this research is descriptive quantitative by collecting data from several sources by means of interviews, observations, and distributing questionnaires to a sample that has been determined by the researcher, namely staff who are entitled to company imprest funds to achieve company goals. The application of the Fluctuating Balance Method at PT Syngenta Indonesia Station Kediri is in accordance with the applicable regulations. Recording is done immediately after the transaction. Top up is done at any time and will always fluctuate according to the needs of the company's expenses. The problem that occurs in these companies lies in the recording process which is carried out directly after the transaction. And this is done to avoid proof of transactions. Imprest fund system implementation in company should start with more careful and better billing. So that the recording made at the end of a certain period is not a problem and has an impact on other problems.